The ethno-mathematization in the development of the logical mathematical thought of the teachers of secondary education of the educational institutions of the district of Amarilis – Huánuco - Ortega-Mallqui, Arnulfo (2019)
The purpose of the present investigation was to determine the influence of the ethno-mathematization in the development of the logical mathematical thought of the teachers of secondary education of the educational institutions of the district of Amarilis - Huánuco. It was developed an explanatory investigation of design almost experimental, correlational causal; It was worked with a control group and an experimental group. In which, with the teachers of the educational institution Cesar Vallejo of the district of Amarilis as the experimental group it was developed the application of the ethno-mathematization since March to June of 2009 and was taken like the control group of teachers of secondary education of the educational institution El Amauta José Carlos Mariátegui of Paucarbambilla - Amarilis. The results of the Post Test, about the Mathematic Logical thought so as in the control group as in the experimental group is observed that they are different; since in the first one the majority of the 93.4% it concentrates among Start, Process and Intermediate and in the second the majority of the 86.7% it concentrates among Intermediate, Sufficient and Distinguish. Therefore, in the control group the results spread toward Start and Process with the interval of scores between six and eleven, while in the experimental group the results spread toward Sufficient and Distinguish with the interval of scores between 15 and 18. Which, shows the positive influence of the ethno-mathematization in the development of the Logical mathematical thought. In conclusion, the value of Z = 6.52 is located to the right of Z = 1.96 that is the zone of refusal, therefore we rule out the null hypothesis and we accept the alternate hypothesis; that is to say it is shown that the ethno-mathematization influences positively in the development of the logical mathematical thought of the teachers of the educational institutions of secondary education of the district of Amarilis - Huánuco.